Phase Composition and Magnetic Behaviour of Iron Sand from Syiah Kuala Beach Prepared by Mechanical Alloying - Zulkarnain Jalil; Eva Novita Sari; Ismail A B; Erfan Handoko (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2016)
It has recently been investigated that ball milling can improve the magnetic properties of natural iron sand significantly. In this work, we present the phase composition and magnetic behavior of iron sand from Syiah Kuala Beach, Banda Aceh. Samples were prepared by mechanical alloying method using a Fritsch planetary ball mill for 20 hours. As the results, it was shown by XRD testthat Fe3O4 (magnetite) appears as the majority phase and the magnetic properties observation shown that the magnetization saturation (Ms) and remanent (Br) was decreased with the increasing of the coercivity (Hc).